Modelling of corroding concrete structures Proceedings of the Joint fib-RILEM Workshop held in Madrid, Spain, 22-23 November 2010 - Andrade, Carmen; Mancini, Giuseppe 1940- (RILEM bookseries, 2011)
These are the papers presented at the Fib-RILEM workshop held in Madrid, Spain, in November 2010. The assessment of deterioration and aging of concrete structures, most commonly through reinforcement corrosion, is not considered in current structural codes or standards. Some guidelines manuals exist, and research has been done, but there is as yet no accepted methodology nor models that could be used by engineers. This book deals with all aspects related to modelling of corroding structures and provides state-of-the-art information on structural models for corroding structures.